Lossless Data Compression of Wireless Sensor in Bridge Inspection System - Ni, Zhengsong; Cai, Shuri; Ni, Cairong (Sensors and materials, 2024)
In bridge inspection using wireless technology, the sensor node carries very limited energy. In this paper, data compression technology to reduce the amount of communication data by sacrificing data accuracy is introduced. The lossless data compression algorithm was chosen as the algorithm of the bridge inspection system, and the algorithm was further improved. In addition, we compared the compression rates and execution times of the Huffman, Lempel–Ziv– Storer–Szymanski (LZSS), and improved Lempel–Ziv–Welch (LZW) algorithms. The results showed that the improved LZW algorithm is highly adaptable, accommodates any type of input data, and can make full use of the repeatability of data. Therefore, this lossless data compression algorithm is suitable for application in the wireless sensor networks of bridge inspection systems.